Isolating the Symbolic Implications of Employee Mobility: Price Increases after Hiring Winemakers from Prominent Wineries - Roberts, Peter W; Khaire, Mukti; Rider, Christopher I (American Economic Review, 2011)
Because wines are aged for several years before they are released, newly hired winemakers arrive as wines made by their predecessors enter the market. An analysis of winemaker hiring events reveals that wines released right after a new winemaker's arrival from a prominent competitor are priced significantly higher than corresponding wines released in the preceding year. However, the wines released before and after the hiring event are indistinguishable in terms of quality. These findings isolate a “purely symbolic” effect of employee mobility, which affirm sociological accounts of markets—under conditions of uncertainty, inter-organizational affiliations condition producers' returns to quality demonstrations.